AKTA OTENTIK RAPAT UMUM PEMEGANG SAHAM (RUPS) MELALUI MEDIA TELEKONFERENSI (MEKANISME PEMBUATAN DAN KEKUATAN PEMBUKTIANNYA) - Rizkianti, Wardani (Jurnal Yuridis, 2016)
While the times and technology, the implementation of the GMS alsoundergone a transformation from conventional systems towards the use ofelectronic systems with the use of telecommunications technology. Asstipulated in Article 77 of the Company Law which legitimacy implementationof the GMS teleconferencing and mandated obligation of making the minutesof the meeting . Viewed from one side , Article 77 of the Company Lawprovides legitimacy in making authentic deed AGM via media teleconferenceon the other hand there is disharmony with the related regulations , especiallyLaw Notary No. 30 of 2004 ( UUJN ) and Law No. 2 of 2014 on AmendmentAct No. 30 of 2004 concerning Notary ( UUJN - P) , giving rise to concernsregarding the exact mechanism and strength of evidence. This study is a firststep in reforming the national legal framework in order to accommodate thedynamics of telematics technology in a deed in Indonesia .